Satire`s techniques in Akbar Eksir`s poets - Yahya Sheikhi; Ahmad Ghanipour Malekshah; SIAVASH HAGHJOU; aliakbar bagheri khalili (مطالعات زبانی و بلاغی)
Humor is one of the most effective critical strategies in poem and prose. Some humorists use this kind of literature in order to reveal and reform the discursive, behavioral and intellectual deficiencies of a person or society. In so doing, they use a sugar-coated pill so that the audience would willingly accept it. Akbar Eksir is a contemporary poet whose works intermingle with humor through the employment of a simple, mild, and artistic language. He reminds us of the individual and social problems, hoping that they would be resolved. This research project aims to study the techniques of humor in Eksir’s poetry, trace some samples for each and then analyze them. The results of the study show that his books "Please Sit Down, Dear Chair", “Honeybees Have Got Diabetes", “Dead Pistachio Is Crushing Silence", “Fertile Grasshoppers", “Malaria", and “Makataonashim” have used some methods like hyperbole, understatement, incongruity and comparison, linguistic plays, surprise, inverted collocations, etc. The results show that linguistic plays and incongruity/comparison are the most widely used methods.